Neoadjuvant hyperthermic intraperitoneal chemotherapy: impact on chemotherapy response score and prognosis in high-grade serous ovarian carcinoma - Feng, Xiaojie; Wang, Yuhua; Li, Han; Zhang, Ye; Li, Lei; Ma, Yanying; Wang, Shanping; Wang, Li (Frontiers in Oncology, 2025)
BackgroundThis study aimed to assess the therapeutic effects of neoadjuvant hyperthermic intraperitoneal chemotherapy (NHIPEC) combined with neoadjuvant chemotherapy (NACT) in patients with high-grade serous ovarian carcinoma.MethodsThis study used a retrospective cohort design. A total of 120 patients with ovarian cancer who received NACT and underwent interval debulking surgery (IDS) at our hospital between 2016 and 2018 were enrolled in this study. Thereinto, 67 patients received the NHIPEC combined with the NACT regimen, and the remaining 53 patients received only NACT as the control. The degree of tumor burden reduction in patients treated with different regimens was evaluated using the chemotherapy response score (CRS), and patient survival data were analyzed.ResultsWe found that the combination with NHIPEC is independently and positively correlated with a CRS reaching grade 3 (P=0.002), indicating that the combined treatment regimen has a significant advantage in improving the tumor response rate. Moreover, NHIPEC is an independent favorable prognostic factor for overall survival (OS) (P=0.032) and progression-free survival (PFS) (P=0.029). Further analysis showed that the median OS and PFS of patients receiving the combined treatment regimen were extended to 40 and 16 months, respectively, compared with 34 and 15 months in the group receiving only NACT. In addition, the incidence of grade 3-4 adverse events is comparable between the two groups.ConclusionThis study supports the notion that the treatment regimen of NHIPEC combined with NACT can improve tumor response in advanced ovarian cancer compared with NACT alone.